(untitled) (Journal of actual problems of jurisprudence, 2019)
The development o fi nsittutionofecological in Kazakhstan is a veryimportantmechanismbecauseoftheproblemsofpolutionofthenatu ralenviroment and lowinvestment in precations and liqudationoftheemergencysituations in totheenviromentalsafety. The practice in the insuranceallowstoconcludethat in Kazakhstan sel fi nsurancedevelopspoorlybecauseofmanyproblems. Currentlytheattentionisfocusedont heproblemsofcoordinationoftherisksinthesphereofthenaturalenviroment and naturalresourceuse.